Exploring how to sustain 'place-based' rural health academic research for informing rural health systems: a qualitative investigation - Belinda O'Sullivan; Alice Cairns; Tiana Gurney (BMC, 2020)
Abstract Background The field of rural health research is critical for informing health improvement in rural places but it involves researching in small teams and distributed sites that may have specific sustainability challenges. We aimed to evaluate this to inform how to sustain the field of rural health research. Methods We conducted In-depth semi-structured interviews of 50-70 minutes with 17 rural early career researchers who were from different research sites across rural Australia. Data were thematically coded. Results Seven sustainability challenges were noted, namely recognition, workload, networks, funding and strategic grants, organisational culture, job security, and career progression options. Rural researchers were poorly recognised for their work and researchers were not extended the same opportunities enjoyed by staff at main campuses. Unpredictable and high workloads stemmed from community demand and limited staff. Strategic grant opportunities failed to target the generalist, complex research in this field and the limited time researchers had for grant writing due to their demands within small academic teams. Limited collaboration with other sites increased dissatisfaction. In the face of strong commitment to rural 'places' and their enthusiasm for improving rural health, fixed-term contracts and limited career progression options were problematic for researchers and their families in continuing in these roles. Conclusion A comprehensive set of strategies is needed to address the sustainability of this field, recognising its value for rural self-determination and health equity. Hubs and networks could enable more cohesively planned, collaborative research, skills sharing, senior academic supervision and career development. Targeted funding, fit to the context and purpose of this field, is urgent. Inaction may fuel regular turnover, starting after a researcher's first years, losing rich academic theoretical and contextual knowledge that is essential to address the health of rural populations.